Mesenchymal Stem Cells With Cancer-Associated Fibroblast-Like Phenotype Stimulate SDF-1/CXCR4 Axis to Enhance the Growth and Invasion of B-Cell Acute Lymphoblastic Leukemia Cells Through Cell-to-Cell Communication - Pan, Chengyun; Fang, Qin; Liu, Ping; Ma, Dan; Cao, Shuyun; Zhang, Luxin; Chen, Qingzhen; Hu, Tianzhen; Wang, Jishi (Frontiers in Cell and Developmental Biology, 2021)
Background: Bone marrow mesenchymal stem cells (BM-MSCs) are the stromal cells in the leukemia microenvironment, and can obtain cancer-associated fibroblast (CAF)-like phenotype under certain conditions to further promote leukemia progression. However, the mechanism of MSCs with CAF-like phenotype interacting with leukemia cells in B-cell acute lymphoblastic leukemia (B-ALL) and promoting the progression of B-ALL remains unclear. Methods: MSCs with CAF-like phenotype were obtained by treating MSCs with recombinant human transforming growth factor-β (rhTGF-β), hereafter referred to as TGF-β conditioned MSCs. In vivo mouse model experiments, in vitro transwell chamber experiments, three-dimensional (3D) cell culture models, lentiviral transfection and other experimental methods were used to investigate the possible mechanism of the interaction between TGF-β conditioned MSCs and leukemia cells in promoting the growth, migration and invasion of B-ALL cells. Results: Compared with untreated MSCs, TGF-β conditioned MSCs significantly promoted the growth and proliferation of leukemia cells in mice, and increased the expression of CXCR4 in tumor tissues. In vitro cell experiments, TGF-β conditioned MSCs obviously promoted the migration and invasion of Nalm-6/RS4;11 cells, which were effectively blocked by the CXCR4 inhibitor AMD3100, thereby inhibiting the secretion of MMP-9 in TGF-β conditioned MSCs and inhibiting the activation of the PI3K/AKT signaling pathway in leukemia cells. Further, findings were made that the interaction between TGF-β conditioned MSCs and leukemia cells were mediated by the interaction between the integrin receptor α5β1 on the surface of leukemia cells and the increased expression of fibronectin on TGF-β conditioned MSCs. AMD3100 could weaken such effect by reducing the expression of integrin α5β1 on leukemia cells. Further regulation of integrin β1 could effectively interfere with the interaction between TGF-β conditioned MSCs and leukemia cells. Conclusions: MSCs with CAF-like phenotype could be a key factor in promoting the growth and invasion of B-ALL cells, and the SDF-1/CXCR4 axis might be a significant factor in mediating the communication of MSCs with CAF-like phenotype and leukemia cells. To prevent the progression of B-ALL cells, blocking the SDF-1/CXCR4 axis with AMD3100 or targeting integrin β1 might be a potential therapeutic strategy.